Factors affecting the efficiency of energy-saving projects in market conditions - Kurbanov, F.; Tyll, L. (BUKETOV BUSINESS REVIEW, 2019)
The article discusses the factors affecting energy-saving projects including administrative, legislative, economic, social and environmental, scientific and technical and other processes. The authors of the article note that the introduction of energy-saving projects is associated with significant capital costs, which include the replacement of technologies and reconstruction of existing production, the introduction of less energyintensive materials, reduction of the material and electrical capacity of products due to innovations. The article classifies the factors affecting energy-saving projects by the degree of influence and the nature of the impact. All factors influencing the efficiency of energy saving regime implementation in real life are divided into two groups: subjective (psychological, motivational, and informational) and objective (social, investment, technological). The article indicates the tax (decrease or increase of the general level of taxation; tax discounts on investment projects; a variety of special tax incentives) and economic (introduction of a system of loans, grants, instalment payments, concessional and interest-free energy efficiency loans; promoting energy efficiency through environmental mechanisms of influence; attraction of investments into development of energy saving potential due to saving resources for the future) tools to encourage energy conservation. The authors of the article classify the factors by the nature of the impact on energy-saving projects: technical and technological factors; organizational factors (legislative and regulatory, informational and analytical); socio-economic factors (financial and economic, motivational and stimulating).